Unusual Case of Colonic Intussusception Caused by Angiolipoma: Case Report and Literature Review - Lino, Hugo Araujo; Hubbard, Brittany; LePhan, Huy; Mahoney, Sean; Harrel, Nicholas (Journal of Coloproctology, 2024)
Angiolipomas are benign tumors composed of adipose tissue commonly found in the subcutaneous tissue with vascular proliferation. It is uncommon to find it in the gastrointestinal tract. This report focuses on an angiolipoma found in the sigmoid colon causing intussusception in a young healthy 26-year-old male. We discuss the presentation, workup and surgical management.
Keywords: Angiolipoma; intussusception; tumor; abdominal mass; adipose tumor